Divergent and convergent modes of interaction between wheat and Puccinia graminis f. sp tritici isolates revealed by the comparative gene co-expression network and genome analyses - Rutter, William B.; Salcedo, Andres; Akhunova, Alina; He, Fei; Wang, Shichen C.; Liang, Hanquan Q.; Bowden, Robert L.; Akhunov, Eduard (My University, 2017)
Background: Two opposing evolutionary constraints exert pressure on plant pathogens: one to diversify virulence factors in order to evade plant defenses, and the other to retain virulence factors critical for maintaining a compatible interaction with the plant host. To better understand how the diversified arsenals of fungal genes promote interaction with the same compatible wheat line, we performed a comparative genomic analysis of two North American isolates of Puccinia graminis f. sp. tritici (Pgt). Results: The patterns of inter-isolate divergence in the secreted candidate effector genes were compared with the levels of conservation and divergence of plant-pathogen gene co-expression networks (GCN) developed for each isolate. Comprative genomic analyses revealed substantial level of interisolate divergence in effector gene complement and sequence divergence. Gene Ontology (GO) analyses of the conserved and unique parts of the isolate-specific GCNs identified a number of conserved host pathways targeted by both isolates. Interestingly, the degree of inter-isolate sub-network conservation varied widely for the different host pathways and was positively associated with the proportion of conserved effector candidates associated with each sub- network. While different Pgt isolates tended to exploit similar wheat pathways for infection, the mode of plant-pathogen interaction varied for different pathways with some pathways being associated with the conserved set of effectors and others being linked with the diverged or isolate-specific effectors. Conclusions: Our data suggest that at the intra-species level pathogen populations likely maintain divergent sets of effectors capable of targeting the same plant host pathways. This functional redundancy may play an important role in the dynamic of the "arms-race" between host and pathogen serving as the basis for diverse virulence strategies and creating conditions where mutations in certain effector groups will not have a major effect on the pathogen's ability to infect the host.
Citation: Rutter, W. B., Salcedo, A., Akhunova, A., He, F., Wang, S. C., Liang, H. Q., . . . Akhunov, E. (2017). Divergent and convergent modes of interaction between wheat and Puccinia graminis f. sp tritici isolates revealed by the comparative gene co-expression network and genome analyses. Bmc Genomics, 18, 20. doi:10.1186/s12864-017-3678-6
Keywords: Wheat Resistance; Stem Rust; Comparative Genomics; Gene Co-Expression; Network; Stem Rust